Development, opportunities, and challenges of siRNA nucleic acid drugs - Bowen Xiao; Shaopeng Wang; Yu Pan; Wenjun Zhi; Chensheng Gu; Tao Guo; Jiaqi Zhai; Chenxu Li; Yong Q. Chen; Rong Wang (Molecular Therapy: Nucleic Acids)
Small interfering RNA (siRNA) drugs were first proposed in 1999. They have reached the market for administration to patients after more than 20 years of development. The US Food and Drug Administration has approved six siRNA drugs in recent years: patisiran, givosiran, lumasiran, vutrisiran, inclisiran, and nedosiran. siRNA drugs are based on the post-transcriptional gene regulation mechanism of RNA interference. These drugs have gained widespread attention for their effectiveness, low dosage, and low frequency of administration. Theoretically, siRNA drugs have great potential due to their ability to silence almost any target gene. However, drug delivery, especially the extrahepatic one, remains a major challenge. Currently, all approved drugs target the liver. The high blood flow, natural filtration function, and drug delivery methods of the liver overall ensure high efficacy and stability of the drugs themselves. This review summarizes the history of siRNA drug development and the mechanisms of action, with a focus on the drug targets, indications, and key clinical trial results to introduce the status of both marketed drugs and those currently in clinical trials. Additionally, this review provides a brief analysis of several key stages of the commercialization process of siRNA drugs.